If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -11 = 5x + 1 Reorder the terms: -11 + 2x = 5x + 1 Reorder the terms: -11 + 2x = 1 + 5x Solving -11 + 2x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -11 + 2x + -5x = 1 + 5x + -5x Combine like terms: 2x + -5x = -3x -11 + -3x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 -11 + -3x = 1 + 0 -11 + -3x = 1 Add '11' to each side of the equation. -11 + 11 + -3x = 1 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 1 + 11 -3x = 1 + 11 Combine like terms: 1 + 11 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 0y=-4 | | X+15=x*4 | | 7x-(2x+3)=9(x-1) | | Xa+15=x*4 | | 3x+1=4x+8 | | x+8x=3+x | | Y+y+15=23 | | 15/10x4= | | y=-1X+20 | | f(1)=5x^2+100 | | -.2(1-x)=4(4+.1x) | | f(x)=5x^2+100 | | 28078.82+0.9010x+17491.84+0.8746x+8489.33=0.9563x+19126.34+26237.77+0.8489x+8489.33 | | X/22=4/11 | | 0=r+10 | | 8.13=x | | -7x+6y=-24 | | -7x+6x=-24 | | 3(5x-1)=50 | | -2=0.666x-x | | 48x+20y=6 | | ln(9)+ln(x-10)=3 | | -10r^2-3r+12= | | 69x^2+27=0 | | 4x+6y=124 | | 5x+3y+6z=42 | | y=0.05(x-30)+6 | | 0.2x+6=1.2x | | y=0.05(x-30)2+6 | | 6x+2y+4z=36 | | 2^3(x-3/4)-12=2 | | -10v^2-4p^2+5h^2= |